TEACHING DESCRIPTIVE READING BY USING SURVEY, QUESTION, READ, WRITE AND (SQRW) STRATEGY TO THE TENTH GRADE STUDENTS OF SMA MUHAMMADIYAH 1 PALEMBANG - marlen rahmawati (Edukasi, 2017)
The objectives of this study are to find out whether or not there is a significant improvement before and after the treatment on the tenth grade students’ reading comprehension scores of SMA Muhammadiyah 1 Palembang by using SQRW strategy and to find out whether or not there is a significant difference on the tenth grade students’ reading comprehension scores of SMA Muhammadiyah 1 Palembang between the students who are taught by using SQRW strategy and those who are not. This study used quasi-experimental design using nonequivalent pretest-posttest design. There were 68 students from class X MIPA 4 and X MIPA 6 chosen as the sample. In collecting the data, test was used. The test was given twice to experimental and control groups, for pretest and posttest. To verify the hypotheses, the data of pretest and posttest were analyzed by using independent sample t-test and paired sample t-test in SPSS 18 program. The findings showed that the p-output from paired sample t-test (sig2-tailed) was 0.000 which was lower than 0.05, and t-value 11.294 was higher than t-table (34-1) with df=33 (2.034). The result of p-output from independent sample t-test was 0.003 which was lower that 0.05 and the t-value 3.104 was higher than t-table (68-2) with df=66 (1.996). Therefore it could be stated that teaching reading descriptive text by using SQRW strategy had significant improvement and showed significant difference on the students’ reading comprehension scores.